Endogenous electric fields as guiding cue for cell migration - Funk, Richard H. W. (Frontiers in Physiology, 2015)
This review is about the long-range action of endogenous electric fields (EF) within animal organisms. It covers two major topics: 1) the different functions of the EF during development of the organism as well as physiological and pathological roles of EF and 2) cell migration under the guiding cue of EF. It should be noted that EF arise within the plasma membrane of each cell type (including eukaryotic non–neural animal cells). By their nature, EF are not action potentials like in nerve cells but electric potentials of low magnitude and slow fluctuation. In particular, we discuss the role of EF in early embryogenesis, during embryo patterning and during cells migration and differentiation. Also in wound healing EF are able to concert cell migration. The action of EF during regeneration is reported with a discussion of the different ways EF spread long-range information. As guiding cues for cell migration EF often override chemical or topographic cues. In osteoblasts, for instance the directional information of EF is captured by charged transporters on the cell membrane and transferred into signaling mechanisms modulating the cytoskeleton and motor proteins resulting in a persistent directional migration. In conclusion it could be shown that EF exert different important functions in multicellular animal organisms. Future research should focus on the mechanisms how EF signals are transferred into classical biochemical and cell biological signaling routes. EF are not only static, however their rhythms are still elusive. Also nearly nothing is known about the nature of EF within the interior of cells. Moreover, further investigation in all spheres of EF action has the great potential to develop new concepts for therapy including the field tumor genesis.